MENURUNKAN KELUHAN MUSKULOSKELETAL PADA GURU SMA MELALUI PELATIHAN PEREGANGAN OTOT DITEMPAT KERJA - Dini Nur Alpiah; Firdausiyah Amallia, Bayu Febrianto, Hasya Khairina Afrida, Nyimas Najwa Putri RK (JOURNAL OF COMMUNITY DEDICATION, 2025)
Musculoskeletal disorders are often experienced by teachers due to non-ergonomic physical demands, static work positions, and repetitive activities. Long-term teaching activities and administrative tasks are the main risk factors. Community service aims to identify efforts to prevent and treat musculoskeletal disorders. The method used is quantitative descriptive to see the effects before and after muscle stretching. The results of Community Service activities for teachers showed a decrease in the average musculoskeletal complaints before 52.3 and after becoming 38.9, proven to be effective in overcoming the problem of musculoskeletal pain disorders